Search for narrow high-mass resonances in proton-proton collisions at 8 TeV decaying to a Z and a Higgs boson - Bernardes, Cesar [UNESP] (My University, 2016)
We present a search in the CMS detector for an exotic high-mass and narrow resonance decaying into a Z and a Higgs from standard model in the final state with a pair of tau leptons and a pair of quarks. We analyze 19.7/fb of integrated luminosity of proton-proton collisions at √ s = 8 TeV from LHC. In the resonance mass range of interest (0.8-2.5 TeV), the Z and Higgs bosons are produced with large momentum compared with their masses, which implies that the final products of the two quarks and the two tau leptons must be detected within a small angular separation. Jet substructure techniques are used to identify the boosted Z boson decaying hadronically and a modified approach is considered to reconstruct very collimated pairs of tau leptons from boosted Higgs decay. From a combination of all possible decay modes of the tau lepton, heavy spin-1 resonances production cross sections are excluded at 95% C.L. in a range between 0.9 and 27.8 fb, depending on the resonance mass.